Serum trace metals in Pre-Eclamptic Nigerians - Ikaraoha, Ikechukwu Chidiebere; Mbadiwe, Nkeiruka Chigaekwu; Anetor, John Ibhagbemien; Ojareva, Isreal Agware (Asian Journal of Medical Sciences, 2016)
Background: The role of trace metals in Pathogenesis of Pre-eclampsia has received insufficient attention in Nigeria. Materials and Methods: We examined the effect of serum levels of some trace metals; selenium (Se), zinc (Zn), copper (Cu), cobalt (Co), and manganese (Mn) in the development of pre-eclampsia in Nigeria. Blood samples were collected from 59 pre-eclamptic, 150 normal pregnant and 122 non pregnant women. Serum Se, Zn, Cu, Co and Mn were determined by AAS. Results: Result shows significantly lower serum Se, Zn, Cu, Cu: Zn ratio, Co and Mn in pre-eclamptics compared to normal pregnant women (p<0.001). Comparison of normal pregnant women and controls showed non significant difference in the zinc level (P>0.05), significantly lower levels of serum Se, Co, Mn (p<0.00011, p=0.0022, p<0.0001 respectively) and significantly raised copper level (p<0.001) in normal pregnant women compared to controls. Serum Se, Zn, Co and Mn were significantly lower (p<0.001) while serum copper and Cu: Zn ratio were significantly higher (p<0.001) in pregnant women compared to controls. ANOVA shows significant progressive decreases in serum Se, Zn Co and Mn, from controls to normal pregnant women and pre-eclamptics (p<0.0001). Conclusion: Decreases in serum level of Se, Zn, Cu, Cu: Zn ratio, Co and Mn may play important role in the pathogenesis of pre-eclampsia. Asian Journal of Medical Sciences Vol. 7(3) 2016 78-83